2011
DOI: 10.1089/ten.teb.2010.0472
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes in Animal Models: A Systematic Review on Toxic Potential

Abstract: Amongst the engineered nanomaterials, especially carbon nanotubes (CNTs) have received considerable attention for application in tissue engineering scaffolds. CNTs are considered promising on behalf of their physicochemical properties, yet such nanomaterials also have been associated with potentially hazardous effects on human health. To gain insight into the toxicity aspects of CNTs in vivo, the present study presents a systematic review of literature. After screening of literature through defined inclusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 94 publications
0
50
1
Order By: Relevance
“…Till date, cyto- and bio-compatibility studies using pristine WSNTs and WSNT-reinforced PPF nanocomposites have not been reported, and thus are currently in progress. There is now a wide body of published work on the cyto- and bio- compatibility of carbon nanotubes [41, 42]. Additionally, few studies also report the in vitro and in vivo bio-compatibility of SWCNTs-reinforced PPF nanocomposites [43] and porous scaffolds [9, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Till date, cyto- and bio-compatibility studies using pristine WSNTs and WSNT-reinforced PPF nanocomposites have not been reported, and thus are currently in progress. There is now a wide body of published work on the cyto- and bio- compatibility of carbon nanotubes [41, 42]. Additionally, few studies also report the in vitro and in vivo bio-compatibility of SWCNTs-reinforced PPF nanocomposites [43] and porous scaffolds [9, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Several CNT-based systems have been developed for siRNA delivery [95] and they generally demonstrated a high delivery efficiency. However, in the past few years their toxicity has been under serious scrutiny [96]. The key issue surrounds their resemblance to asbestos fibers in terms of the high aspect ratio and, hence, pathogenic effects [97].…”
Section: Nanotoxicity Of the Major Classes Of Sirna Carriersmentioning
confidence: 99%
“…191 We conducted a bone implantation study of MWCNTs used as scaffolds for bone regeneration and as biomaterials in contact with bone. After implanting MWCNTs in bone defects artificially made in mouse tibias, we observed normal bone repair, with incorporation of MWCNTs particles into repaired bone substrate.…”
Section: Present Status Of Research Into the In Vivo Toxicity Of Cntsmentioning
confidence: 99%